ROAD TRAFFIC ACCIDENTS IN BANDUNG, INDONESIA - Prasidhawaty, Triss
This study was concerned with the classification and analysis of 430 road traffic accidents in Bandung which occurred from March, 1983 to February, 1984. The data used in the study were those recorded by the police for the state insurance company, as these were more detailed than regular police records. 75 per cent of all accidents reported to the police were recorded on the insurance forms. There were 1.7 serious accidents to every fatal accident, and it appears that accidents were under-reported in Bandung, particularly the less severe ones, and damage only accidents. The data were not always of a quality suitable for traffic engine-ering purposes, in particular the precision of accident location. An Australian system of classifying ancidents proved too detailed and a simpler alternative was devised. To help provide more data suitable for the traffic engineer, a new standard accident recording form was suggested. Traffic in Bandung is mixed, and includes many types of motorized paratransit vehicles and pedal-driven trishaws. A particular feature is the very large number of motorcycles, which have a reputation for careless driving. The study found that motorcycle accidents were very common; two thirds of all accidents involved at least one motorcycle, and they were also involved in nearly half of all pedestrian accidents. One accident in five was between a motorcycle and a car. There was some evidence that motorcycle lights, particularly rear ones, were often not used at night. Only 1 in 4 accidents occurred at intersections. A small number of links and intersections showed more accidents than the rest, and the report includes suggestions for specific safety improvements at the worst sites .